CONTRIBUTION TO THE ETNOGRAPHY OF SERBIAN-ALBANIAN RELATIONS IN ŠAR MOUNTAINS PARISH SIRINIĆ: A VIEW FROM THE POINT OF THE LOCAL SERBS (Heritage, 2024)
The author of this paper presents part of the results of his field research in Šar Mountains Parish Sirinić, a region in the extreme south of Kosovo and Metohija. Starting from the fact that in Sirinić beside to the majority Serbs also live Albanians, thanks to what this region has the character of an ethnically mixed area, the attention in the paper is paid to the consideration of local Serbian-Albanian relations in the context of the position of the Serbs living in Sirinić in the conditions of socio-political processes in Kosovo and Metohija after the NATO aggression on FR Yugoslavia in 1999 until today. The studied problem was observed from the perspective of the local Serbs, which means that in achieving the goal of the research the emphasis was placed on the analysis of the discourse of the members of the researched Serbian community. The results presented in the paper were obtained on the basis of field research conducted in Sirinić on several occasions during 2023 and 2024. What results of research indicated is the complexity of the studied topic, since the inter-ethnic relations in the observed area reflected the relationship between the members of the two ethnic groups inherited from the period before 1999, while, at the same time, they were under the influence of diametrically different positions of Serbs and Albanians in Kosovo and Metohija after the mentioned year, which reflected the position of power of the Albanian side over the Serbian side. Serbian-Albanian relations in Sirinić, according to the perception of local Serbs, manifested one main characteristic, which could probably be best described by the term ambivalence, which means that relations to their Albanian neighbors the members of the researched Serbian community most often experienced through the prism of the relations in which they intertwined coexistence and cooperation, on the one hand, and mutual distrust, on the other.
Keywords: Sirinić, Serbs, Albanians, Serbian-Albanian relations, Kosovo and Metohija